Exploring the external exposome using wearable passive samplers - The China BAPE study. (1st February 2021) - Koelmel, Jeremy P.; Lin, Elizabeth Z.; Guo, Pengfei; Zhou, Jieqiong; He, Jucong; Chen, Alex; Gao, Ying; Deng, Fuchang; Dong, Haoran; Liu, Yuanyuan; Cha, Yu'e; Fang, Jianlong; et al.
Abstract: Environmental exposures are one of the greatest threats to human health, yet we lack tools to answer simple questions about our exposures: what are our personal exposure profiles and how do they change overtime (external exposome), how toxic are these chemicals, and what are the sources of these exposures? To capture variation in personal exposures to airborne chemicals in the gas and particulate phases and identify exposures which pose the greatest health risk, wearable exposure monitors can be deployed. In this study, we deployed passive air sampler wristbands with 84 healthy participants (aged 60–69 years) as part of the Biomarkers for Air Pollutants Exposure (China BAPE) study. Participants wore the wristband samplers for 3 days each month for five consecutive months. Passive samplers were analyzed using a novel gas chromatography high resolution mass spectrometry data-processing workflow to overcome the bottleneck of processing large datasets and improve confidence in the resulting identified features. The toxicity of chemicals observed frequently in personal exposures were predicted to identify exposures of potential concern via inhalation route or other routes of airborne contaminant exposure. Three exposures were highlighted based on elevated toxicity: dichlorvos from insecticides (mosquito/malaria control), naphthalene partly from mothballs, and 183 polyaromatic hydrocarbons from multiple sources. Other exposures explored in this study are linked to diet and personal care products, cigarette smoke, sunscreen, and antimicrobial soaps. We highlight the potential for this workflow employing wearable passive samplers for prioritizing chemicals of concern at both the community and individual level, and characterizing sources of exposures for follow up interventions. Graphical abstract: Image 1 Highlights: Wristband passive samplers were used to detect 615 personal chemical exposures. Exposure profiles of adults (aged 60–69) were most strongly associated with temperature. In colder months, exposures increased from cooking, cleaning, and household products. In warmer months, mosquito repellent, sunscreen, and second-hand smoke dominated exposures.